Incorporation of Label into Pollen Tube Walls from Myoinositol-labeled Lilium longiflorum Pistils - Kroh, M. (1970)
Compatible and incompatible pollen tubes growing on detached Lilium longiflorum pistils which had been prelabeled with myoinositol-U-(14)C take up a portion of the label and utilize it for biosynthesis of tube wall substance. The label is transferred from pistil to pollen tubes apparently via the secretion products (exudate) of the pistil. The exudate thus appears to have a major nutritional role in pollen tube growth in vivo.